Explaining the differences in firm level production capacity realization in Bangladesh food manufacturing: a panal data study - Salim, Ruhul (Tennessee State University, 2007)
The aim of this paper is to examine the impact of a set of firm-specific and policy related variables such as size, age, ownership and effective rate of assistance on the rate of production capacity realization (PCR) of firms. This study uses a panel of 92 food manufacturing firms of Bangladesh over the periods of 1992 - 1994 and 1997 - 1999. Firm size is found to have positive impact while capital intensity and age of firm have negative impact on PCR at the firm level. The striking result is that the policy related variables such as the effective rate of assistance (ERA) and outward orientation (OPN) do not have any significant impact on PCR. These results are confirmed by the extensive test of sensitivity analysis. The insignificance of ERA and OPN may be attributed to piecemeal and partial nature of policy reforms. The results suggest the need for further reform of trade policies, in particular, focusing on reducing nominal and effective protection levels in order to enhance competition and competitiveness so than an efficient production can take a firmer root in the industrial sector of the economy.